Chromoendoscopy versus autofluorescence imaging for neoplasia detection in patients with longstanding ulcerative colitis (FIND-UC): an international, multicentre, randomised controlled trial. (May 2018) - Vleugels, Jasper L A; Rutter, Matt D; Ragunath, Krish; Rees, Colin J; Ponsioen, Cyriel Y; Lahiff, Conor; Ket, Shara N; Wanders, Linda K; Samuel, Sunil; Butt, Faheem; Kuiper, Teaco; Travis, Simon P L; et al.
Summary: Background: Patients with longstanding ulcerative colitis undergo regular dysplasia surveillance because they have an increased colorectal cancer risk. Autofluorescence imaging and chromoendoscopy improve dysplasia detection. The aim of this study was to determine whether autofluorescence imaging should be further studied as an alternative method for dysplasia surveillance in patients with longstanding ulcerative colitis. Methods: This prospective, international, randomised controlled trial included patients from an ulcerative colitis-dysplasia surveillance cohort from five centres in the Netherlands and the UK. Eligible patients were aged 18 years or older who were undergoing dysplasia surveillance after being diagnosed with extensive colitis (Montreal E3) at least 8 years before study start or with left-sided colitis (Montreal E2) at least 15 years before study start. Randomisation (1:1) was minimised for a previous personal history of histologically proven dysplasia and concomitant primary sclerosing cholangitis. The coprimary outcomes were the proportion of patients in whom at least one dysplastic lesion was detected and the mean number of dysplastic lesions per patient. The relative dysplasia detection rate, calculated as the ratio of the detection rates by autofluorescence imaging and chromoendoscopy, needed to be more than 0·67 (using an 80% CI) for both primary outcomes to support a subsequent large non-inferiority trial. Outcomes were analysed on a per-protocol basis. The trial is registered at the Netherlands Trial Register, number NTR4062. Findings: Between Aug 1, 2013, and March 10, 2017, 210 patients undergoing colonoscopy surveillance for longstanding ulcerative colitis were randomised for inspection with either autofluorescence imaging (n=105) or chromoendoscopy (n=105). Dysplasia was detected in 13 (12%) patients by autofluorescence imaging and in 20 patients (19%) by chromoendoscopy. The relative dysplasia detection rate of autofluorescence imaging versus chromoendoscopy for the proportion of patients with ulcerative colitis with at least one dysplastic lesion was 0·65 (80% CI 0·43–0·99). The mean number of detected dysplastic lesions per patient was 0·13 (SD 0·37) for autofluorescence imaging and 0·37 (1·02) for chromoendoscopy (relative dysplasia detection rate 0·36, 80% CI 0·21–0·61). Adverse events were reported for two patients in the autofluorescence imaging group (one patient had intraprocedural mild bleeding, and one patient had abdominal pain) and for three patients in the chromoendoscopy group (two patients had intraprocedural mild bleeding, and one patient had perforation). Interpretation: Autofluorescence imaging did not meet criteria for proceeding to a large non-inferiority trial. Therefore, existing autofluorescence imaging technology should not be further investigated as an alternative dysplasia surveillance method. Funding: Olympus Europe and Olympus Keymed.